Food peptidomics of in vitro gastrointestinal digestions of partially purified bovine hemoglobin: low‐resolution versus high‐resolution LC‐MS/MS analyses. Issue 13 (21st April 2016) - Caron, Juliette; Chataigné, Gabrielle; Gimeno, Jean‐Pascal; Duhal, Nathalie; Goossens, Jean‐François; Dhulster, Pascal; Cudennec, Benoit; Ravallec, Rozenn; Flahaut, Christophe
Abstract : Consumers and governments have become aware how the daily diet may affect the human health. All proteins from both plant and animal origins are potential sources of a wide range of bioactive peptides and the large majority of those display health‐promoting effects. In the meat production food chain, the slaughterhouse blood is an inevitable co‐product and, today, the blood proteins remain underexploited despite their bioactive potentiality. Through a comparative food peptidomics approach we illustrate the impact of resolving power, accuracy, sensitivity, and acquisition speed of low‐resolution (LR)‐ and high‐resolution (HR)‐LC‐ESI‐MS/MS on the obtained peptide mappings and discuss the limitations of MS‐based peptidomics. From in vitro gastrointestinal digestions of partially purified bovine hemoglobin, we have established the peptide maps of each hemoglobin chain. LR technique (normal bore C18 LC‐LR‐ESI‐MS/MS) allows us to identify without ambiguity 75 unique peptides while the HR approach (nano bore C18 LC‐HR‐ESI‐MS/MS) unambiguously identify more than 950 unique peptides (post‐translational modifications included). Herein, the food peptidomics approach using the most performant separation methods and mass spectrometers with high‐resolution capabilities appears as a promising source of information to assess the health potentiality of proteins.